Preparation and characterization of cobalt-60 glass microspheres for radioactive particle tracking applications. (July 2022) - Biswal, Jayashree; Pant, Harish Jagat; Sharma, Vijay Kumar; Joseph, Annie; Ananthanarayanan, Arvind
Abstract: The current work describes development and optimization of a process for preparation of cobalt-60 glass microspheres. These microspheres have potential for applications in radioactive particle tracking (RPT) studies in multiphase flow systems. In the first step of preparation, soda lime glass containing 5–10 wt% cobalt oxide was produced through melt-quench method. Subsequently, cobalt glass microspheres (CMSs) were prepared by microwave heating of tiny glass grains in presence of graphite. In the final step, radioactive cobalt-60 microspheres (RMSs) were produced by neutron irradiation of the CMSs in a nuclear reactor. The CMSs were characterized for surface morphology, elemental composition, homogeneity, crystalinity using SEM, EDX and XRD, respectively. The thermal behaviour of the microspheres was characterized by TG and DSC analysis. The size distribution of CMSs analyzed by SEM was found to be in the range 500–2000 μm. The preparation step was optimized to produce adequate activity in a single microsphere, so that they can be utilized for RPT applications. Graphical abstract: Image 1 Highlights: A melt-quench process was developed for preparation of cobalt-60 glass microspheres. Spheroidization was done by microwave heating through interfacial polarization. The size of the microspheres confirmed by SEM was in the range 500–2000 μm. The microspheres with 10% CoO were semi-crystalline in nature. The produced 60 Co microsphere was devoid of any radionuclide impurity.